"Why Should Our Bodies End at the Skin?": Embodiment, Boundaries, and Somatechnics - SHILDRICK, MARGRIT (Hypatia, 2015)
Donna Haraway's enduring question—"Why should our bodies end at the skin?" (Haraway 1990, 220)—is ever more relevant in the postmodern era, where issues of bodies, boundaries, and technologies increasingly challenge not only the normative performance of the human subject, but also the very understanding of what counts as human. Critical Disability Studies has taken up the problematic of technology, particularly in relation to the deployment of prostheses by people with disabilities. Yet rehabilitation to normative practice or appearance is no longer the point; instead, the lived experience of disability generates its own specific possibilities that both limit and extend the performativity of the embodied self. I look at what is at stake in the challenge to the Western logos that comes specifically from the capacities of the disabled body, understood not as a less than perfect form of the normative, but as figuring difference in a nonbinary sense. Feminist theory has long contested the isomorphism of the logos, but I go beyond simply setting out the grounds for revaluing multiple variant forms. The feminist turn to Jacques Derrida and Gilles Deleuze opens up the problematic to a celebratory positioning of difference and transcorporeality as the very conditions of life.
Keywords: EDI; approches et analyses; arts; bioéthique; corps; cours; discipline; philosophie; postmodernisme; premier cycle; prothèses; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; technologie; thématiques; études critiques du handicap; études littéraires

Histoire de la sexualité. 1: La volonté de savoir - Foucault, Michel (Collection tel, 2014)
"L'Histoire de la sexualité, articulée en trois volumes (La volonté de savoir, L'usage des plaisirs et Le souci de soi), prolonge les recherches entreprises avec L'archéologie du savoir et Surveiller et punir. Michel Foucault concentre ses analyses sur la constellation de phénomènes que nous désignons par le « sexe » et la sexualité. L'axe de cette entreprise n'est pas de s'ériger contre une « répression » de la sexualité afin de la « libérer », mais de montrer comment la vie sexuelle a enclenché une volonté systématique de tout savoir sur le sexe qui s'est systématisée en une « science de la sexualité », laquelle, à son tour, ouvre la voie à une administration de la vie sexuelle sociale, de plus en plus présente dans notre existence.Foucault fait ainsi l'archéologie des discours sur la sexualité (littérature érotique, pratique de la confession, médecine, anthropologie, psychanalyse, théorie politique, droit, etc.) depuis le XVIIIe siècle et, surtout, au XIXe, dont nous héritons jusque dans les postures récentes de « libération sexuelle ». L'attitude de censure et celle d'affranchissement se rencontrent finalement dans le même type de présupposé : le sexe serait cause de tous les phénomènes de notre vie comme il commanderait l'ensemble de l'existence sociale."-- Site de l'éditeur.
Keywords: 1800-1899; 1900-1999; approches et analyses; cours; discipline; har4600; histoire et politique; incontournable; philosophie; postmodernisme; premier cycle; périodes historiques; sciences humaines; sexualité; soc2014; thématiques